Fabrication and Characterization of Modified PVDF Membrane Using TiO2 for Wastewater Containing Paracetamol - Zainiyah, Isti Faizati; Yuniarto, Adhi; Fairuzi, Intania Ika; Purwanti, Ipung Fitri; Marsono, Bowo Djoko (Tecno Scientifica Publishing, 2025)
Modified membranes have gained significant attention due to their ability to enhance performance. Although membranes modified with TiO₂ nanoparticles have been studied, no research has specifically addressed their effectiveness in removing paracetamol contaminants, despite the widespread use of paracetamol and its potential contribution to increased waste production. Therefore, in this study, polyvinylidene fluoride (PVDF) membranes were modified with TiO₂ nanoparticles, providing new insights into the use of PVDF-TiO₂ specifically for paracetamol wastewater treatment. The results showed that TiO₂ nanoparticle-modified membranes exhibited better performance than unmodified membranes. The unmodified membrane had a lower performance rate (69.18%) compared to membranes modified with titanium isopropoxide (TTIP) at concentrations of 1 M (93.35%) and 0.5 M (90.05%). These results were supported by Scanning Electron Microscopy (SEM) analysis, which revealed that the unmodified membrane had an average pore size of 0.998 μm, whereas the membranes modified with TTIP at 1 M and 0.5 M had average pore sizes of 0.615 μm and 0.791 μm, respectively. The larger pores in the unmodified membrane allowed larger particles to pass through, reducing its filtration efficiency. These findings underscore the potential of TiO₂ nanoparticle-modified membranes for significantly enhancing water purification processes, particularly in the removal of pharmaceutical contaminants like paracetamol. Ultimately, this research could contribute to the development of more effective strategies for managing pharmaceutical waste in water sources, leading to improved environmental protection and public health.